Sleep Before and After Retirement - Myllyntausta S; Stenholm S (My University, 2025)
In this review, we focus on the association of sleep and retirement from two perspectives. Firstly, we examine the role of sleep during the working years on retirement timing. Secondly, we examine how sleep changes during the transition to retirement.\nPersons with sleep difficulties are more likely to retire due to health problems, such as depression and musculoskeletal disorders. Retirement, on the other hand, is associated with both increased sleep duration and decreased sleep difficulties, mainly premature awakenings and nonrestorative sleep.\nPromotion of sleep quantity and quality could be a potential way to support employees' work ability and possibly even to postpone retirement, at least in relation to early retirement. Possible proposed mechanisms for the improved sleep after retirement include removal of work stress and increased flexibility in time use, which could be targeted in attempt to promote adequate and good quality of sleep already during the working years.\nPurpose of Review\nRecent Findings\nSummary